PENGEMBANGAN BAHAN AJAR DIGITAL SEJARAH NASIONAL INDONESIA BERBASIS KAKAWIN NEGARAKRETAGAMA UNTUK MENINGKATKAN KEMAMPUAN EKSPLANASI SEJARAH MAHASISWA PROGRAM STUDI PENDIDIKAN SEJARAH FKIP UNIVERSITAS JEMBER - Romadloni, Sahru; Sariyatun, S.; Joebagio, Hermanu (HISTORIKA, 2016)
Indonesia as a nation can’t separated from its history, each event has historical heritage like inscriptions, building, literature work, documents and others. During the learning process Indonesia's National History, especially on material the history of the kingdom of Majapahit, still considered less attractive because often memorize, should explanation of history needed to an event. Besides considered boring, the teaching of history also considered not to follow technological development. Even though technological development can be combined with needs the teaching of history. Kakawin Negarakertagama classified historical heritage which gives information related background development until the time Majapahit empire heyday. Through the improvement of digital learningn sources of indonesian national history based kakawin negarakertagama to increase the student’s ability of historical explanation in history education program, Education and Teaching Facultty, Jember University.Design the improvement of digital learning sources of Indonesian National History based on Kakawin Negarakertagama arranged by procedure ADDIE which consist of five rare. stages in research includes a preliminary study, the improvement of digital learning sources, and effectiveness test. Data analysis feasibility digital learning sources using likert scale with a range 1 until 5, whereas the effectiveness test for t test independent sample t test on program spss 19. T test on test the ability of explanation of history earned value 6,631 with significant level 0,000 (0,000< 0,025), meaning there significant influence toward digital learning sources developed, so that class experiment better than class control. So digital learning sources developed effective to improve the ability of historical explanation.